Konsistensi Will dan Thing-in-Itself: Menafsir Ulang Metafisika Schopenhauer - Mustika, I Ketut Sawitra; Harsawibawa, Albertus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2021)
This article aims to present a different reading from the mainstream interpretation that corners Schopenhauer: a consistent interpretation. The authors use a method of acquiring knowledge by acquaintance and description. Schopenhauer’s theory is often considered inconsistent because it concludes will as a thing-in-itself. The will, which is obtained through direct observation of the body, is a representation that is still shrouded in the veil of time form, while thing-in-itself is completely different from representation, and is beyond the reach of space, time, and causality, with reference to principle of sufficient reason. Concluding will as a thing-in-itself is therefore considered inconsistent. However, this interpretation might be wrong because Schopenhauer never claimed that direct observation of the body would yield knowledge of the thing-in-itself. From the very beginning, he realised that direct knowledge of thing-in-itself was impossible, because the knowledge, regardless of its form, was always knowledge of appearances. He knows that will does not qualify as a thing-in-itself. The true function of the will in Schopenhauer's metaphysics lies in the name and concept by which one can think about thing-in-itself objectively.